ENVIRONMENTAL CONSTRAINTS IMPOSED ON PLASTIC WASTE OF WEEE DISMANTLING MANAGEMENT - POPIȚA, Gabriela-Emilia; POPOVICI, Antoanela; ROȘU, Cristina; SMICAL, Irina (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Waste Electric and Electronic Equipment (WEEE) is a special stream of waste, due to the required collection, treatment and recycling conditions. The legislative collection ratio imposed in EU per inhabitant/year is 4 kg; therefore, an increase of collected amount of WEEE is expected. Plastics represent an important flow of dismantled WEEE and an appropriate management of it is requested, due the content in brominated fire retardants compounds. Even the environmental politics are very restrictive in the use of the hazardous compounds in the manufacture of EEE (Electric and Electronic Equipment), these substances are present in the waste, at the product end of life. The aim of this study is to present the environmental risks correlated with the legislative constraints for plastic waste of WEEE, in order to highlight the importance of an appropriate management and of recycling methods.